PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN POLA BILANGAN BERBANTUAN ISPRING SUITE TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Nurfika Mato; Syamsu Qamar Badu; Franky Alfrits Oroh (LPPM Universitas Bina Bangsa, 2024)
The purpose of this study was to determine the effect of the use of ispring suite assisted number pattern learning media on the mathematics learning outcomes of class VIII students. This research is a quantitative research using experimental methods and using a pretest-posttest control group design. Sampling used the Random Sampling technique and the selected classes were class VIII-6 as the experimental class and class VIII-4 as the control class. The research instrument uses a learning achievement test in the form of a description/essay. Inferential analysis was performed using the anacova test. The results showed that there was a positive and significant effect on the use of iSpring Suite assisted number pattern learning media on students' mathematics learning outcomes